Pengaruh waktu pencetakan kompon polipropilene untuk acuan sepatu - Hs, Sunarso; Surip, hernadi (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1991)
Polypropylene is the most important polymer in poliolafine. In this study polypropylene is added with kaolin, in the batch, the varied time used for moulding was 13, 15, 17 19, and 21 minutes, while the temperature and pressure was 190 C, 150 kg/cm2.The porpuse of the varied time used is to detect how for the influence of time to words of hardness and impact resistance of polypropylene prepared for shoe last.It can be found from the result that time does not have influence on the impact resistance of polypylene compound used for shoe last, but the longer the time used the hardness will be decreased.The highest test result of hardness and impact resistance was achived by polypropylene compound which was moulded in 13 minutes (75,53 shore D, 2,5831 kg cm/cm).